Evaluation Operational of Reduce Reuse Recycle Waste Treatment Facility (TPS 3R) in Bandung City (Case Study: TPS 3R Saling Asih and TPS 3R Hikmah) - Permatasari, Arindita Dessi; Setyanto, Djoko (Bina Nusantara University, 2025)
Waste is a problem faced by the city where currently waste is still being transported to landfill without any waste processing first. Currently, Bandung City has a waste management problem because it does not have a final disposal site (TPA) especially for waste reduction at the source and currently the waste is processed at the Sarimukti Regional Landfill, West Bandung Regency. Currently, the achievement of waste reduction in Bandung City reached 14.46% (SIPSN, 2023). The purpose of this study is to determine the operational performance of TPS3R in Bandung City as a waste treatment facility. This research was conducted at two TPS 3R in Bandung City, namely TPS 3R Saling Asih II, Maleer Village and TPS 3R Hikmah, Panjunan Village. The method in this study uses quantitative through data collection carried out on the operational conditions of TPS 3R management of 5 aspects waste management in accordance with the. Technical Guidelines for the Implementation of Reduce Reuse Recycle Waste Treatment Facility Activities (2021). From the results of this study it is known that the operational status of the management of TPS 3R Saling Asih II is in very good condition and TPS 3R Hikmah is in good condition. Optimization of TPS 3R can be done through the formation of competent community groups through various training and monitoring of operational performance of TPS 3R.